EPub styling essentials. (Wiley, 2013)
"Master ePub Styling on your terms with this one-of-a-kind video training course. ePub is the industry-standard for creating scalable e-books for viewing on a variety of mobile devices. Now you can learn the ins and outs of styling your own ePub files--from using a text editor to adding multimedia with ePub Styling Essentials. Our instructors provide expert, straight-forward, user-friendly training to help you tackle new topics the way you want to learn. Master basic skills, boost your creativity, and challenge yourself in bold new directions. Understand the CSS Box Model and HTML and CSS tag and class styles Create custom headings and use embedded fonts, Add hyperlinks, page breaks, tables, and graphics Validate and troubleshoot your ePubs. Includes over 2-1/2 hours of ePub Styling video training. If you're looking for real-world ePub Styling instruction, you'll find it here."--Resource description page